2007
DOI: 10.1126/science.1140170
|View full text |Cite
|
Sign up to set email alerts
|

Domesticated Nature: Shaping Landscapes and Ecosystems for Human Welfare

Abstract: Like all species, humans have exercised their impulse to perpetuate and propagate themselves. In doing so, we have domesticated landscapes and ecosystems in ways that enhance our food supplies, reduce exposure to predators and natural dangers, and promote commerce. On average, the net benefits to humankind of domesticated nature have been positive. We have, of course, made mistakes, causing unforeseen changes in ecosystem attributes, while leaving few, if any, truly wild places on Earth. Going into the future,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
440
1
23

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 789 publications
(464 citation statements)
references
References 30 publications
0
440
1
23
Order By: Relevance
“…England also has no wilderness regions (sensu Sanderson et al 2002). It is thus a good example of the type of 'domesticated nature' (Kareiva et al 2007) that will increasingly describe locations where much of the world's population lives. In addition, England represents a good test of the effectiveness of different types of conservation strategies in delivering ecosystem services because protected areas, restrictive zoning and incentive payment schemes are all well developed, covering over 35 per cent of the total terrestrial area (130 439 km 2 ) (figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…England also has no wilderness regions (sensu Sanderson et al 2002). It is thus a good example of the type of 'domesticated nature' (Kareiva et al 2007) that will increasingly describe locations where much of the world's population lives. In addition, England represents a good test of the effectiveness of different types of conservation strategies in delivering ecosystem services because protected areas, restrictive zoning and incentive payment schemes are all well developed, covering over 35 per cent of the total terrestrial area (130 439 km 2 ) (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Scott et al 2001;Loucks et al 2008), and consequently will receive only some benefits from many of the ecosystem services delivered by such areas. Indeed, an increasing number of regions are so densely populated that they entirely lack extensive wilderness areas, including parts of the eastern seaboard of the USA, southeast Asia, western Europe, the Atlantic forests of Brazil and large parts of India (Kareiva et al 2007). The need to protect ecosystem services within human-dominated landscapes has been recognized by practitioners; a recent survey showed that conservation projects that focus on ecosystem service provision in addition to biodiversity protection are more likely to be found in agricultural landscapes than those that focus on biodiversity conservation alone (Goldman et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, little attention has been paid to hydrographic change at broader spatial scales, where distinct patterns and processes may emerge (Heffernan and others 2014;Thorp 2014). A broader assessment of how urbanization changes the channel and water body abundance, distribution, and form (hydrography) in cities is essential to understanding both the environmental constraints on land-use change (Dunne and Leopold 1978) and the environmental and societal consequences of rapid and ongoing urbanization of human populations and landscapes (Paul and Meyer 2001;Cohen 2003;Foley and others 2005;Kareiva 2007;Grimm and others 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all of the studies in this topic have used an individual-function perspective to examine the relationship between biodiversity and a certain ecosystem function. In fact, most ecosystems are maintained and valued by a series of ecosystem functions and services (Kareiva et al 2007;Srivastava and Vellend 2005). The use of an individual function as proxy for overall ecosystem functions may ignore other important functions and underestimate the potential risk of biodiversity loss in influencing the overall ecosystem functions (Gamfeldt et al 2008).…”
mentioning
confidence: 99%